PELATIHAN LAPORAN KEUANGAN PERUSAHAAN JASA DI SMA SANTO KRISTOFORUS 1 - Wirianata, Henny; Sari, Vinnetta Ratna; Patricia, Virginia; Lie, Irene Kim; Widjaja, Karen (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Today's young generation needs to have financial literacy from an early age, one of which is about preparingfinancial reports. Understanding the preparation of financial reports can help awaken the entrepreneurial spirit inhigh school students. SMA Santo Kristoforus 1 has provided accounting lessons but is limited to grade 12 studentsonly. Based on an agreement with partners, UNTAR Community Service (CS) Team will provide accounting training,especially on how to prepare financial statements for service companies at SMA Santo Kristoforus 1. The trainingwill be conducted of line in 2 sessions with a duration of 2 hours from 14.45-16.45. The first session was held onFriday, 8 September 2023 and the second session was held on Wednesday, 13 September 2023. The trainingparticipants were students of SMA Santo Kristoforus I grades 10 to 12. The training was given in the form ofpresentation of material, practice questions, and quizzes so that participants can understand deeply about thematerial presented. Based on the results of the questionnaire, it can be concluded that the training activities havegone well and the participants were very enthusiastic about taking part in the training held by the UNTAR CS Team.The results of the questionnaire showed that there was an increase in the understanding of the training participantsas seen from the average answer score of 3.91 out of 5 before participating in the training and after participating inthe training it became 4.25 out of 5. The ef ect of this significant increase occurred shows the success of the UNTARCS Team in carrying out training. It is hoped that this training will increase the attractiveness of Santo Kristoforus IHigh School students to study accounting more deeply and be interested in continuing to higher education in theaccounting study program. ABSTRAK: Generasi muda saat ini perlu memiliki literasi keuangan sejak dini, salah satunya adalah tentang penyusunan laporankeuangan. Dengan memahami penyusunan laporan keuangan dapat membantu membangkitkan jiwa kewirausahaanpada siswa/i SMA. SMA Santo Kristoforus 1 telah memberikan pelajaran akuntansi tetapi terbatas pada siswa/ikelas 12 saja. Berdasarkan kesepakatan dengan pihak mitra, Tim PKM UNTAR akan memberikan pelatihanakuntansi khususnya tentang cara penyusunan laporan keuangan perusahaan jasa di SMA Santo Kristoforus 1.Pelatihan dilakukan secara tatap muka sebanyak 2 pertemuan dengan durasi 2 jam dari pukul 14.45-16.45.Pertemuan pertama dilakukan pada hari Jumat, 8 September 2023 dan pertemuan kedua dilakukan pada hari Rabu,13 September 2023. Peserta pelatihan adalah siswa/i SMA Santo Kristoforus I kelas 10 sampai 12. Pelatihandiberikan dalam bentuk pemaparan materi, latihan soal, dan kuis agar peserta dapat memahami materi yangdisampaikan. Berdasarkan hasil kuesioner dapat disimpulkan bahwa kegiatan pelatihan telah berjalan dengan baikdan peserta pun sangat antusias mengikuti pelatihan yang diadakan oleh Tim PKM UNTAR. Hasil dari kuesionermenunjukan bahwa adanya peningkatan pemahaman dari peserta pelatihan yang dilihat dari dari rata-rata nilaijawaban sebesar 3,91 dari 5 sebelum mengikuti pelatihan dan setelah mengikuti pelatihan menjadi 4,25 dari 5.Pengaruh peningkatan yang cukup signifikan terjadi menunjukkan keberhasilan Tim PKM UNTAR dalammenjalankan pelatihan. Dengan pelatihan ini diharapkan akan meningkatkan daya tarik para siswa/i SMA SantoKristoforus I untuk mempelajari akuntansi lebih dalam dan tertarik untuk melanjutkan ke pendidikan tinggi diprogram studi akuntansi.